Cooperation in social dilemmas: Social norms and cognitive processes - Ortiz, María Victoria (2019)
The purpose of this study was to analyze the role of social norms and cognitive processes in cooperative decisions in a non-probabilistic self-selected sample of Psychology freshmen attending the Universidad Nacional de Córdoba (Argentina). Two studies were conducted (Study 1: n = 124; Study 2: n = 104). In both of them a factorial design implemented in 2 phases was used: (a) cooperative environment and non-cooperative environment, using the Prisoner's Dilemma Game (PDG) and (b) time response conditions (Study 1) or cognitive load conditions (Study 2). In this stage participants played the Public Goods Game. The level of cooperation in the second stage was the main dependent variable. Student' t test, logistic and linear regression analyses, and univariate and multivariate analyses of variance were carried out. The manipulation for generating several social norm environments was not effective. Multiple effects on cooperation were observed depending on which indicators of cognitive processing were considered. The main finding of this study is an interaction effect between the social norm environment and the cognitive load condition in the first PDG round (Study 2)